Características dos profissionais em sistemas de informação: região de Trás-os-Montes (Portugal) - Pereira, João Paulo (2010)
The profile of the Information Systems Professionals remains a constant challenge for schools and employers. Constant environmental, technological and organizational changes may raise difficulties in keeping the curriculum of Information Systems updated. Thus, the knowledge and the abilities demanded of professionals are in constant transformation. School plays an essential role in the process of providing professionals with the necessary skills to operate in the Information Society. Their competence depends, largely, on an appropriate curriculum that must be adequate to the organizations necessities. This paper identifies the skills required for the IS professionals in the organizations located in the region of “Trás-os-Montes” (Portugal). This work is based in a survey, realized in 51 organizations from “Trás-os-Montes”. The main objective was the identification of the skills expected from the employers for the IS professional. The study show that the soft skills are the most required.